Implementasi Manajemen Bisnis Dalam Novel Lupus: Lupus n’Work Karya Hilman - Anantaprima, Fachrezi; Baehaki, Fikri Imam; Kurniawan, Eva Dwi (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Business management is the science and practice that encompasses planning, organizing, directing, and controlling organizational resources to achieve established goals. It involves coordinating various aspects of business activities to ensure the sustainability, growth, and success of the organization. In the novel titled "Lupus N’Work" by Hilman, Lupus and his friends intend to establish a business that arises from their desire not to depend on others and to increase their allowances. However, as their business progresses, a new and more formidable business competitor emerges due to their seriousness. The aim of this research is to determine the implementation of business management by Lupus in Lupus N’Work and to examine whether it aligns with the Business Management Process according to Sarinah. The research method used is the Qualitative Research method, involving a series of steps, including in-depth data collection, analysis, and interpretation. The results obtained using qualitative research methods indicate that the Management Process is in line with the business management process outlined in the book "Introduction to Management" by Sarinah.